2010
DOI: 10.1073/pnas.0914925107
|View full text |Cite
|
Sign up to set email alerts
|

Folding of a transcriptionally acting PreQ 1 riboswitch

Abstract: 7-Aminomethyl-7-deazaguanine (preQ 1 ) sensitive mRNA domains belong to the smallest riboswitches known to date. Although recent efforts have revealed the three-dimensional architecture of the ligand-aptamer complex less is known about the molecular details of the ligand-induced response mechanism that modulates gene expression. We present an in vitro investigation on the ligand-induced folding process of the preQ 1 responsive RNA element from Fusobacterium nucleatum using biophysical methods, including fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
135
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 44 publications
9
135
0
1
Order By: Relevance
“…The kinetics of the structural changes from fold  A to fold  B ( k A→B ), and from fold  B to fold  A ( k B→A ), were determined from the single‐exponential fit of the distributions of τ Stem and τ Loop , respectively. The revealed kinetics of conformational switching between fold  A and fold  B structures were in the same order as for the preQ 1 induced structural switching rate obtained from stopped‐flow measurements 48. The addition of 1 μ m preQ 1 resulted in an increase in k A→B , while k B→A was almost unaffected.…”
supporting
confidence: 61%
“…The kinetics of the structural changes from fold  A to fold  B ( k A→B ), and from fold  B to fold  A ( k B→A ), were determined from the single‐exponential fit of the distributions of τ Stem and τ Loop , respectively. The revealed kinetics of conformational switching between fold  A and fold  B structures were in the same order as for the preQ 1 induced structural switching rate obtained from stopped‐flow measurements 48. The addition of 1 μ m preQ 1 resulted in an increase in k A→B , while k B→A was almost unaffected.…”
supporting
confidence: 61%
“…These estimates, which are based on local structural rearrangements of the RNA that report indirectly on the ligand binding process, are in line with the parameters reported previously for a number of other riboswitch aptamer domains (for comparison, see table S1 in ref. 22). Strikingly, the estimated k on for the truncated, ΔP4/A 3 construct was ∼1.6 ± 0.1 × 10 6 M −1 ·s −1…”
Section: Significancementioning
confidence: 96%
“…Correspondingly, the preQ 1 -II riboswitch represents a putative target for antibiotic intervention. Although preQ 1 class I (preQ 1 -I) riboswitches have been extensively investigated (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), preQ 1 class II (preQ 1 -II) riboswitches have been largely overlooked despite the fact that a different mode of ligand binding has been postulated (14).…”
mentioning
confidence: 99%
“…While this study demonstrates the role of RNA sequence on interhelical dynamics and flexibility, little is known about the dynamic properties of ssRNA-helix junctions at the atomic level, even though they are often important sites for conformational changes and adaptation, particularly for systems containing pseudoknots (Kim et al 2008;Cao and Chen 2009;Cash et al 2013). The dynamic properties of ssRNA-helix junctions are of particular interest in the transcription-regulating prequeuosine riboswitch aptamer because the ssRNA tail must fold back onto the helix to form a pseudoknot to allow efficient cotranscriptional binding to ligand (Kang et al 2009;Klein et al 2009;Spitale et al 2009;Rieder et al 2010;Suddala et al 2013). Our previous studies on the isolated 12-nt ssRNA indicated a degree of order within the ssRNA that may facilitate rapid docking into the minor groove of the adjacent helix in the presence of ligand (Eichhorn et al 2012a); however, these studies neglected the effect of the ssRNA-helix junction.…”
Section: Introductionmentioning
confidence: 99%